The Effect of Health Education with Video Media on Mother's Knowledge about Complementary Foods - Febrianti Febrianti; Ana Mariza; Riyanti Riyanti; Yuli Yantina (Universitas Malahayati Lampung, 2024)
ABSTRACT Weaning foods are additional food given to babies after the age of six months to 24 months old. The proportion of consumption of various weaning foods in children aged 6-23 months only reached 46.6% and in Srimulyo Village 4 mothers (80%) did not know the stages of giving weaning foods. Health education is an effort to increase mothers' knowledge about weaning foods. The objective of this research is to determine the effect of health education using videos on mothers' knowledge about weaning foods in Srimulyo Village in the work area of Bandar Negeri Suoh Public Health Center in 2023. This study was quantitative research using a pre-experimental method with the one-group pretest and posttest design. The population in this study were 30 mothers who had babies aged 0-6 months in Srimulyo Village in the work area of Bandar Negeri Suoh Public Health Center. The sample in this study was 30 people. A total sampling technique was used in this study. Then, the data were analyzed using the Wilcoxon test. The results of this study indicated that the mean score of mothers' knowledge about weaning foods before being given health education using videos was 68.03 and after being given health education increased to 89.9. Then, the results of the Wilcoxon test obtained a p-value of 0.000 0.05, meaning that there was an effect of health education using videos on mothers' knowledge about weaning foods in Srimulyo Village in the work area of Bandar Negeri Suoh Public Health Center in 2023. An effect of health education using videos on mothers' knowledge about weaning foods in Srimulyo Village in the work area of Bandar Negeri Suoh Public Health Center in 2023. Keywords: Weaning Foods, Health Education, Knowledge